What has been driving work-to-work transitions in the emerging world? A comparative study of Indonesia and South Africa - Johannes Brehm; Angela Doku; Verónica Escudero (International Labour Organization (ILO), 2023)
There is little knowledge about the shape, prominence and drivers of work-to-work transitions in low- and middle-income countries. This paper examines these elements in the context of South Africa and Indonesia - two middle-income countries with similar development levels yet different labour market characteristics. We employ a comparative cross-country methodology using long-term panel data. This enables us to examine work-to-work transitions across and within age cohorts and exploit the panel structure of the data through a fixed-effects model to identify the drivers of these transitions. We find that while the prominent transition types differ between the two countries, younger workers have higher transition rates. Moreover, we find that precarious forms of employment are persistent: individuals who start their careers at the bottom of the transition ladder (i.e., in informal work, the agriculture sector or a low-skill occupation) are less likely to transition out of this situation. Finally, we unveil suggestive evidence that computer and socioemotional skills play a role in encouraging certain transitions in South Africa and Indonesia, respectively.
Keywords: 330; work; decent work; employment; informal employment; rural employment; self employment; youth employment; casual work; occupational qualification; skills; economic sectors; research